Reassessment of Olduvai Bed I cercopithecoids: A new biochronological and biogeographical link to the South African fossil record. Issue 92 (March 2016) - Gilbert, Christopher C.; Frost, Stephen R.; Delson, Eric
Abstract: Fossil monkeys have long been used as important faunal elements in studies of African Plio-Pleistocene biochronology, particularly in the case of the South African karst cave sites. Cercopithecoid fossils have been known from Tanzania's Olduvai Gorge for nearly a century, with multiple taxa documented including Theropithecus oswaldi and Cercopithecoides kimeui, along with papionins and colobines less clearly attributable to species. A small number of large papionin fossils, including a partial male cranium and partial female skull, have been previously identified as an early form of Papio, but noted as distinct from extant baboons as well as other fossil Papio species. In 2013 we reviewed the Olduvai cercopithecoid material at the National Museum of Tanzania, with a particular focus on the specimens from Beds I–IV. Quantitative and qualitative comparisons of the Olduvai papionins largely confirmed previous observations, with one notable exception. The large papionin taxon from Bed I previously recognized as Papio sp. is more properly recognized as Gorgopithecus major, a taxon previously known only from South Africa. Features shared between the Olduvai specimens and G. major include relatively short and concavo-convex tubular nasals, antero-posteriorly curved upper incisor roots, downwardly curved brow ridges in the midline, and robust zygomatic arches. The recognition of G. major at Olduvai Bed I, a well-known horizon with precise radiometric dates, provides an important biochronological and biogeographical link with South African localities Kromdraai A, Swartkrans Member 1 and possibly Swartkrans Members 2–3 and Cooper's A and D.